Constructing Catholic Women’s Religious Identity through Instagram: A Study of the @walmajelena Account - Rindi Ananda Zulfikar Erada; Yeni Huriani; Busro Busro (Khazanah Theologia, 2024)
Purpose: This study aims to explore how the Instagram account @walmajelena functions as a digital space for expressing the religiosity of Catholic women and to examine how its content shapes the followers’ perspectives, understanding, and spiritual experiences in the digital sphere. Methodology: This study uses a qualitative approach within a sociological and media studies framework with descriptive-analytical methods. Data were collected through digital observation and analysis of content and responses from followers of the account. Findings: The findings reveal that @walmajelena serves as a warm, reflective, and contextual medium of faith expression for Catholic women. Through four major themes—prayer, worship attire, Catholic identity, and faith education—the account constructs a dynamic and participatory spiritual space relevant to younger generations. Interaction between the account owner and her followers illustrates a collective process of religious identity construction, turning social media into a site for the negotiation, affirmation, and internalization of evolving faith values. Research Implications: These findings demonstrate that social media can act as an interactive and dialogical sacred space that empowers lay Catholic women to articulate faith beyond institutional boundaries. The study highlights the need for digital–theological literacy and pastoral accompaniment to ensure that digital evangelization remains both spiritually grounded and contextually relevant. Originality/Value: This research offers an original contribution by applying Berger and Luckmann’s social construction theory to explain how religious identity is dynamically shaped through digital interaction. It also presents a new understanding of female digital religiosity, showing how personal faith narratives evolve into collective expressions of Catholic identity within Indonesia’s plural digital culture.